Almond cold-pressed oil by-product as ingredient for cookies with potential health benefits: Chemical and sensory evaluation - João C.M. Barreira; M. Antónia Nunes; Beatriz Vieira da Silva; Filipa B. Pimentel; Anabela S.G. Costa; M. Alvarez-Ortí; J.E. Pardo; M. Beatriz P.P. Oliveira (Food Science and Human Wellness)
Nowadays, food security is a global concern and a great scientific challenge. Agro-industrial by-products can be used as potential ingredients of innovative food products, contributing to solve this societal demand. By-products of high specialty oils processing, for instance, have remarkable nutritional and organoleptic properties. Accordingly, the partially delipidified almond flour (PDAF) remaining from almond oil extraction, was used as an alternative ingredient in a highly appreciated almond-based cookie (“almendrados”). For comparison purposes, four different “almendrados” formulations (one industrial, two with PDAF, and one with whole almond flour), were compared regarding nutritional composition, vitamin E and fatty acids profiles. To assess the cookie sensory properties, seventy-four consumers evaluated “appearance”, “taste”, “sweetness”, “crunchiness”, “hardness”, “overall quality” using adequate hedonic scales. Fat and protein levels showed significant differences among industrial and the other three samples. Cookies with PDAF presented similar tocopherols and fatty acids to the traditional (more expensive) formulation, besides reaching the highest scores on “appearance”, “sweetness”, “hardness”, “overall quality” and “buying predisposition” parameters. Accordingly, the incorporation of PDAF might represent an effective way of adding value to an industrial by-product, while providing a pleasant novel cookie formulation. Keywords: By-products, Almond, Food security, Cookie formulation, Principal component analysis